How is the availability of public health workers in Indonesia's primary health care? Secondary data analysis of health facility research in 2019 - Dian Mawarni; Sabran Sabran (AOSIS, 2022)
The lack and maldistribution of public health workers are critical issues for primary health care. This study aimed to assess the availability of public health workers at primary health care and to identify its related factors. We use secondary data from health facility research in 2019. Overall, 68.79% of primary health care in rural areas and 71.33% of primary health care in remote areas have the number of public health workers fit standards, but urban areas only reach 46.82%. The public health worker from health promotion and behavior concentration is more dominantly fulfilled than others. Accreditation status is a determinant factor of the availability of public health workers in urban and rural primary health care. Especially remote primary health care, it is not only affected by accreditation status but also service capability. The government needs to review the policy of public health worker recruitment at primary health care to support the fulfillment of public health workers. Public health education should start considering career development programs to ensure that all graduates from various concentrations can be absorbed into the workforce.